Association of Impaired Glucose Regulation and Insulin Resistance With Cardiac Structure and Function: Results From ECHO-SOL (Echocardiographic Study of Latinos). (October 2016) - Demmer, Ryan T.; Allison, Matthew A.; Cai, Jianwen; Kaplan, Robert C.; Desai, Ankit A.; Hurwitz, Barry E.; Newman, Jill C.; Shah, Sanjiv J.; Swett, Katrina; Talavera, Gregory A.; Thai, Ashley; Youngblood, Marston E.; et al.
Abstract : Background—: We examined the relationship between glucose homeostasis and comprehensive measures of cardiac structure and function among a representative sample of US Hispanics. Methods and Results—: ECHO-SOL (Echocardiographic Study of Latinos), an echocardiographic ancillary study of the HCHS/SOL (Hispanic Community Health Study/Study of Latinos), enrolled 1818 Hispanic/Latino men (43%) and women (57%) aged ≥45 years (mean=56). Glucose intolerance was defined as follows: (1) prediabetes: hemoglobin (HbA1c) ≥5.7 and <6.5% and (2) diabetes mellitus: fasting plasma glucose ≥126 mg/dL, 2-hour postload glucose ≥200 mg/dL, HbA1c ≥6.5%, or hypoglycemic agent use. Uncontrolled diabetes mellitus was defined as HbA1c ≥7.0%. Insulin resistance was defined using the homeostatic model assessment for insulin resistance. Echocardiography examinations assessed left ventricular structure and systolic/diastolic function. Multivariable linear and logistic regression models were used. Prediabetes prevalence was 42%, and diabetes mellitus prevalence was 28% (47% uncontrolled). Glucose intolerance was associated with increased left ventricular posterior wall and interventricular septal and relative wall thicknesses (all P <0.05), reduced ejection fraction ( P <0.01), reduced stroke and end-diastolic volumes (both P <0.001), decreased peak E′ velocity (lateral and septal P <0.001), and increased E/E′ ratio (lateral and septal P <0.01). The odds ratios (95% confidence intervals) for diastolic dysfunction among individuals with prediabetes and diabetes mellitus (versus diabetes mellitus free) were 1.36 (0.96–1.9) and 1.90 (1.3–2.8), respectively( P =0.006). Results were consistent for uncontrolled diabetes mellitus versus diabetes mellitus. Homeostatic model assessment for insulin resistance was associated with increased E/E′ ( P <0.001), and greater relative wall thickness and septal thickness (both P <0.05); lower stroke volume ( P <0.0001); and lower peak lateral and septal E′ velocities (both P <0.01). Conclusions—: Glucose intolerance and insulin resistance are associated with unfavorable cardiac structure and function, particularly worsened measures of diastolic function, even before the development of diabetes mellitus. Abstract : Supplemental Digital Content is available in the text.